The impact of the German and French art schools on the drawing of Konstantin Istomin - Goshchanskaya, Olga A. (Actual Problems of Theory and History of Art, 2012)
Konstantin Istomin (1887–1942) was a painter and graphic artist, art professor. He is one of insufficiently studied masters of Soviet art of the first half of the 20th century. In the 1930s he was ranked as formalist, only few of his art works remain. Being primarily a painter, he attached great importance to drawing. Th e German and French art schools decisively influenced his art. The present work aims to investigate their impact on the drawing of Konstantin Istomin.
Keywords: Istomin; painter; drawing; German art school; French art school; Hollosy; Munich; Hildebrand